2002
DOI: 10.1034/j.1399-0004.2002.610405.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive decisions of parents of children with metabolic disorders

Abstract: The Interaction Model of Client Health Behavior (IMCHB) served as a guide for variable selection and instrument development for telephone interviews with 230 parents of children with metabolic disorders. Sociodemographic, psycho-affective and client-professional interaction variables were examined in relation to three outcomes: (1) receptivity to future prenatal diagnosis (56% were receptive); (2) likelihood of terminating an affected pregnancy (10% would); and (3) whether or not the parent had taken measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The importance of supportive social relationships in the adaptation of clients with genetic concerns has been well established (Weil, 2000). However, surveys of satisfaction with the client-provider interaction have tended to yield positively skewed results (Hall & Dornan, 1988;Read, 2002), so alternate strategies that evaluate the process of genetic counseling should be devised (Pilnick & Dingwall, 2001). Skirton's (2001) study showed that the quality of a relationship with one's clinician is an important area of concern to a counselee, and the actual effect of that relationship on psychological adaptation could be assessed with additional items in future studies.…”
Section: Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of supportive social relationships in the adaptation of clients with genetic concerns has been well established (Weil, 2000). However, surveys of satisfaction with the client-provider interaction have tended to yield positively skewed results (Hall & Dornan, 1988;Read, 2002), so alternate strategies that evaluate the process of genetic counseling should be devised (Pilnick & Dingwall, 2001). Skirton's (2001) study showed that the quality of a relationship with one's clinician is an important area of concern to a counselee, and the actual effect of that relationship on psychological adaptation could be assessed with additional items in future studies.…”
Section: Supportmentioning
confidence: 99%
“…Skirton's (2001) study showed that the quality of a relationship with one's clinician is an important area of concern to a counselee, and the actual effect of that relationship on psychological adaptation could be assessed with additional items in future studies. However, surveys of satisfaction with the client-provider interaction have tended to yield positively skewed results (Hall & Dornan, 1988;Read, 2002), so alternate strategies that evaluate the process of genetic counseling should be devised (Pilnick & Dingwall, 2001).…”
Section: Supportmentioning
confidence: 99%
“…Nurse researcher Cox () developed the Interaction Model of Client Health Behavior (IMCHB), which tests health behaviours comprising several factors by handling individual differences in a systematic and comprehensive structure. The IMCHB has been used in a variety of studies on adult health behaviours such as reproductive decision‐making (Read ) and physical activity (Lee & Laffrey ). However, the IMCHB has guided fewer explanatory studies in children's health‐promotion behaviours (Farrand & Cox ) and children's diet and physical activity behaviour (Robinson & Thomas ).…”
Section: Introductionmentioning
confidence: 99%
“…396 Parents of children with metabolic disorders, asked if they would consider screening for future pregnancies, only wished to do so in 56% of cases, but 41% had acted to prevent further affected pregnancies. 397 Only one-quarter of parents of children with cystic fibrosis actually used antenatal testing in a subsequent pregnancy. Women were more likely to accept antenatal screening for cystic fibrosis if they considered themselves to be at risk of having a child with the condition, regarded cystic fibrosis as serious and were willing to terminate a pregnancy if the fetus had cystic fibrosis.…”
Section: Literature Reviewmentioning
confidence: 99%